Identity Legitimacy through Cultural Revitalization of Arab People in Tanjung Pasir Village, Pemulutan, Ogan Ilir, South Sumatra - Fitriah; Ris’an Rusli; Choirun Niswah; Mariam Ivana Prazic (El Tarikh : Journal of History, Culture and Islamic Civilization, 2026)
This study is motivated by an interest in the sustainability of the Arab Bungin Ayeb community’s identity in Tanjung Pasir Village through cultural revitalization amid social change. This study is important because it shows how cultural and religious traditions function as mechanisms of identity legitimation within a multiethnic rural society. This research aims to analyze the forms of cultural revitalization and their function in producing social recognition, symbolic authority, and identity sustainability in a multiethnic rural context. This study employs a qualitative approach with a descriptive-interpretative design. Data were collected through field observations, in-depth interviews with religious leaders, community figures, and residents across generations in Tanjung Pasir Village, as well as documentation studies. Thematic analysis was used to relate empirical findings to the framework of identity legitimation and cultural revitalization. The findings show that cultural revitalization operates through three main pathways: historical legitimation through religious rituals and collective memory, symbolic legitimation through genealogy (nasab), religious figures, and religious arts, and social legitimation through cross-ethnic communal traditions such as rumpak-rumpak and communal feasting. These findings demonstrate that the identity of the Arab Bungin Ayeb community is legitimized through inclusive and dialogical cultural practices, contributing to social cohesion and identity sustainability at the local level.